Expanding Wilson’s information behaviour model using social cognitive theory: A case study - Montazeri, Peymon (Information Research an international electronic journal, 2025)
Introduction. The purpose of this paper is to expand Wilson’s information behaviour model using social cognitive theory and demonstrate its use in understanding information seeking and sharing of doctoral peers in unstructured environments. Method. In this qualitative study, data was collected using twenty in-depth, semi-structured interviews of doctoral students in the social sciences and humanities disciplines. Analysis. The interview data was transcribed, imported into the ATLAS.ti software, and coded using thematic analysis. Findings. The findings demonstrate, first, that the intervening variables of the information behaviour model can fall under person and environment categories of social cognitive theory. Second, most of the variables (i.e., psychological, interpersonal/role related, source characteristics, and environment) can be found in information seeking and sharing behaviour of doctoral peers. Finally, person, environment, and behaviour factors have a reciprocal impact on one another. The environment category is discussed in this paper. Conclusion. This paper demonstrates that social cognitive theory can successfully expand the information behaviour model and make it adaptable to the context of information seeking and sharing among doctoral peers in unstructured environments.